Effectiveness of Roof Structures as Dynamic Vibration Dampers in Buildings under Dynamic Loading - Zeki Midi; Eka Satria; Irsal Oktofirnof; M. Raffi Akbar; Lovely Son; Mulyadi Bur (METAL: Jurnal Sistem Mekanik dan Termal, 2026)
Buildings located in earthquake-prone regions are vulnerable to dynamic responses that may cause severe structural damage if not effectively controlled. One emerging approach for seismic response mitigation is the utilization of roof structures as dynamic damping systems. By appropriately tuning the mass, stiffness, and damping characteristics, roof structures can function as dynamic vibration absorbers through interaction with the main structural system. This study evaluates the effectiveness of roof structures acting as dynamic dampers in reducing the seismic responses of buildings. The research is conducted in two stages. The first stage involves a static analysis of U-shaped metallic dampers using the finite element method to determine stiffness and energy dissipation characteristics based on hysteresis curves obtained from cyclic loading. The second stage consists of a dynamic analysis in which the building structure and roof are modeled as a two-dimensional frame system, with metallic dampers installed between the building and the roof. Damper parameters are adopted from the static analysis results, while the roof mass is analytically determined to ensure its effectiveness as a dynamic damper. Dynamic analyses under earthquake excitation are performed to evaluate the reduction in structural displacement. The results indicate that roof-based damping systems can significantly reduce peak dynamic responses, particularly roof displacement and inter-story drift, demonstrating their potential to enhance the seismic performance of buildings in earthquake-prone regions